Selenium Supplementation Affects Insulin Resistance and Serum hs-CRP in Patients with Type 2 Diabetes and Coronary Heart Disease - Farrokhian, A.; Bahmani, F.; Taghizadeh, M.; Mirhashemi, S. M.; Aarabi, MH; Raygan, F.; Aghadavod, E.; Asemi, Z. (Hormone and Metabolic Research, 2016)
To our knowledge, this study is the first indicating the effects of selenium supplementation on metabolic status of patients with type 2 diabetes mellitus (T2DM) and coronary heart disease (CHD). This study was conducted to evaluate the effects of selenium supplementation on metabolic profiles, biomarkers of inflammation, and oxidative stress of patients with T2DM and CHD. This randomized, double-blind, placebo-controlled trial was performed among 60 patients with T2DM and CHD aged 40–85 years. Participants were randomly divided into 2 groups. Group A received 200 μg selenium supplements (n=30) and group B received placebo per day (n=30) for 8 weeks. Fasting blood samples were taken at the beginning of the study and after 8-week intervention to quantify metabolic profiles. After 8 weeks, compared with the placebo, selenium supplementation resulted in a significant decrease in serum insulin levels (− 2.2±4.6 vs. + 3.6±8.4 μIU/ml, p=0.001), homeostasis model of assessment-insulin resistance (HOMA-IR) (− 0.7±1.3 vs. + 0.9±2.4, p=0.004), homeostatic model assessment-beta cell function (HOMA-B) (− 7.5±17.2 vs. + 15.1±34.5, p=0.002) and a significant increase in quantitative insulin sensitivity check index (QUICKI) (+0.01±0.03 vs. − 0.01±0.03, p=0.02). In addition, patients who received selenium supplements had a significant reduction in serum high-sensitivity C-reactive protein (hs-CRP) (− 1 372.3±2 318.8 vs. − 99.8±1 453.6 ng/ml, p=0.01) and a significant rise in plasma total antioxidant capacity (TAC) concentrations (+ 301.3±400.6 vs. − 127.2±428.0 mmol/l, p<0.001) compared with the placebo. A 200 μg/day selenium supplementation among patients with T2DM and CHD resulted in a significant decrease in insulin, HOMA-IR, HOMA-B, serum hs-CRP, and a significant increase in QUICKI score and TAC concentrations.
Keywords: selenium supplementation; type 2 diabetes mellitus; coronary heart disease; insulin resistance